The Influence of Third Party Funds, Third, And Inflation on the Allocation Financing of Micro, Small, and Medium Enterprises (MSMEs) at Bank Syariah Indonesia - Hadratullah, Hadratullah (CV. Civiliza Publishing, 2025)
Study This aiming For examine : the influence of party funds third and inflation to allocation financing business small and medium in Indonesian Islamic banks period 2021-2023 . This research is study quantitative . Variables in study This is a third party fund Third , inflation and financing of MSMEs. Population in study This is report finance monthly Indonesian Islamic bank. The amount sample as much as 31.Technique analysis used​ is analysis statistics descriptive and assumption testing classic . Research results show that : Party funds third influential in a way partial and significant to financing of MSMEs is shown mark coefficient ( 0.000<0.05 so that Ha is accepted and Ho is rejected . Inflation No influential in a way partial and significant with mark coefficient 0.256<0.05 and value t count 1,160 more big from t table 2.04891 so that Ha is rejected and Ho is accepted , and accordingly simultaneous There is influence and significance of third party funds third and inflation to financing of MSMEs, shown with F value calculated 42.658 more big from F table 3.34. And based on results analysis regression R-Square obtained of 0.968 which means that contribution DPK amount and inflation in a way simultaneous influential to allocation financing MSMEs as big as 96.8%. However the remaining 3.2% is explained by other variables that are not entered in variable study.